Operation and control of the series bridge modular multilevel converter (SBC) for HVDC applications - Martinez Diez, Carlos (2019)
Nowadays, with the increasing demand of electricity, new technologies are being researched to improve the electrical transmission. This is the case of the High Voltage Direct Current (HVDC) transmission, which offers some advantages over the more traditional AC transmission, including long distance power transmission, interconnection of asynchronous networks and off-shore power transmission. The main element of an HVDC system is the power converter, and therefore a lot of research is focused on investigating new converter topologies suitable for HVDC transmission. In the recent years, the modular multilevel concept introduced by the modular multilevel converter (MMC) has led to a new breed of modular multilevel topologies with special application to HVDC systems. The Series Bridge Modular Multilevel Converter (SBC) is in this trend of novel converter topologies that are specially suitable for such application. In particular, this topology has a reduced footprint compared to the MMC, as the number of submodules (SMs) needed for the same converter ratings are about half of the number required in an MMC. This makes the SBC very desirable for applications where the size of the converter station is critical like in off-shore HVDC transmission. This research work investigates the operation and control of the SBC converter under grid balanced and unbalanced conditions (negative sequence grid voltage unbalance) as well as presents the control schemes that support the operation of the grid side converter (on-shore) of an HVDC off-shore transmission system. The validation of the theoretical work has been done by developing a switching simulation model and by the construction of a small-scale SBC prototype. Both simulation and experimental results are presented, showing the correct operation of the converter in the different operating conditions.